SGIP1 is involved in regulation of emotionality, mood, and nociception and modulates in vivo signalling of cannabinoid CB1 receptors - Dvorakova, Michaela; Kubik-Zahorodna, Agnieszka; Straiker, Alex; Sedlacek, Radislav; Hajkova, Alena; Mackie, Ken; Blahos, Jaroslav (British journal of pharmacology, 2021)
BACKGROUND AND PURPOSE: Src homology 3-domain growth factor receptor-bound 2-like endophilin interacting protein 1 (SGIP1) interacts with cannabinoid CB1 receptors. SGIP1 is abundantly and principally expressed within the nervous system. SGIP1 and CB1 receptors co-localize in axons and presynaptic boutons. SGIP1 interferes with the internalization of activated CB1 receptors in transfected heterologous cells. Consequently, the transient association of CB1 receptors with β-arrestin2 is enhanced and prolonged, and CB1 receptor-mediated ERK1/2 signalling is decreased. Because of these actions, SGIP1 may modulate affect, anxiety, pain processing, and other physiological processes controlled by the endocannabinoid system (ECS). EXPERIMENTAL APPROACH: Using a battery of behavioural tests, we investigated the consequences of SGIP1 deletion in tasks regulated by the ECS in SGIP1 constitutive knockout (SGIP1-/- ) mice. KEY RESULTS: In SGIP1-/- mice, sensorimotor gating, exploratory levels, and working memory are unaltered. SGIP1-/- mice have decreased anxiety-like behaviours. Fear extinction to tone is facilitated in SGIP1-/- females. Several cannabinoid tetrad behaviours are altered in the absence of SGIP1. SGIP1-/- males exhibit abnormal behaviours on Δ9 -tetrahydrocannabinol withdrawal. SGIP1 deletion also reduces acute nociception, and SGIP1-/- mice are more sensitive to analgesics. CONCLUSION AND IMPLICATIONS: SGIP1 was detected as a novel protein associated with CB1 receptors, and profoundly modified CB1 receptor signalling. Genetic deletion of SGIP1 particularly affected behavioural tests of mood-related assessment and the cannabinoid tetrad. SGIP1-/- mice exhibit decreased nociception and augmented responses to CB1 receptor agonists and morphine. These in vivo findings suggest that SGIP1 is a novel modulator of CB1 receptor-mediated behaviour.
Keywords: GPCR; Animals; Emotions; pain; Female; receptor kanabinoidní CB1; Receptor, Cannabinoid, CB1; cannabinoid receptor 1; Adaptor Proteins, Signal Transducing; Cannabinoids; ženské pohlaví; Mice, Knockout; myši knockoutované; adaptorové proteiny signální transdukční; emoce; Mice; Affect; kanabinoidy; afekt; myši; Fear; strach; Nociception; tolerance; receptory kanabinoidní; Male; Receptors, Cannabinoid; extinkce (psychologie); anxiety; Extinction, Psychological; nocicepce; zvířata; mužské pohlaví; endocannabinoid system